Chitosan Loaded into a Hydrogel Delivery System as a Strategy to Treat Vaginal Co-Infection - Diego R. Perinelli; Raffaella Campana; Athanasios Skouras; Giulia Bonacucina; Marco Cespi; Francesca Mastrotto; Wally Baffone; Luca Casettari (MDPI AG, 2018)
Polymeric hydrogels are common dosage forms designed for the topical administration of antimicrobial drugs to treat vaginal infections. One of the major advantages of using chitosan in these formulations is related to the intrinsic and broad antimicrobial activity exerted on bacteria and fungi by this natural polymer. Most vaginal yeast infections are caused by the pathogenic fungus Candida albicans. However, despite the anti-Candida activity towards and strains susceptibility to low molecular weight chitosan being documented, no information is available regarding the antimicrobial efficacy of mixed hydrogels in which chitosan is dispersed in a polymeric matrix. Therefore, the aim of the study is to evaluate the anti-Candida activity against eight different albicans and non-albicans strains of a mixed hydroxypropyl methylcellulose (HPMC)/chitosan hydrogel. Importantly, chitosan was dispersed in HPMC matrix either assembled in nanoparticles or in a monomolecular state to eventually correlate any variation in terms of rheological and mucoadhesive properties, as well as anti-Candida activity, with the chitosan form. Hydrogels containing 1% w/w chitosan, either as free polymer chain or assembled in nanoparticles, showed an improved mucoadhesiveness and an anti-Candida effect against all tested albicans and non-albicans strains. Overall, the results demonstrate the feasibility of preparing HPMC/CS mixed hydrogels intended for the prevention and treatment of Candida infections after vaginal administration.